Concurrent infections of cryptosporidium and giardia in dairy farms, Mississippi State, Usa - Surumay Vílchez, Queila; Pote, Linda (Revista Científica de la Facultad de Ciencias Veterinarias)
<!–[if gte mso 9]> Normal 0 21 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–> <!– /* Font Definitions */ @font-face font-family:Helvetica; panose-1:2 11 6 4 2 2 2 2 2 4; mso-font-charset:0; mso-generic-font-family:swiss; mso-font-pitch:variable; mso-font-signature:7 0 0 0 147 0; /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman"; @page Section1 size:595.3pt 841.9pt; margin:70.85pt 3.0cm 70.85pt 3.0cm; mso-header-margin:35.4pt; mso-footer-margin:35.4pt; mso-paper-source:0; div.Section1 page:Section1; –> <!–[if gte mso 10]> <![endif]–> Fecal samples from 290 bovines randomly selected at 19 dairy farms in ten counties of Mississippi state, USA, were examined during May to August 1995 to investigate the prevalence and association of Cryptosporidium and Giardia infections. Oocysts of Cryptosporidium were identified through the technique of Sheater”™s sugar flotation, the acid-fast Kinyoun coloration, and Immunofluorescence assay. Age of animals ranged from 4 days to 8 months. Positive animals were found in 18 (94.7%) farms. From total of 290 analyzed samples, 120 (41.3%) were infected: 69 (57.5%) were positive to Cryptosporidium spp., 54 (45%) were positive to Giardia spp., and 30 (25%) were positive to Eimeria spp. Six calves out 120 were positive to both Cryptosporidium and Giardia infection, four were positive to Cryptosporidium and Eimeria infection, and seven animals just had all of three types of parasites.